Perancangan dan Implementasi Jaringan Komputer Lan dan Wlan dengan Quality of Service - Muhammad Alif Gustav; Mega Pranata (Universitas Indraprasta PGRI Jakarta, 2022)
The internet has an important role in supporting activities against the routines of the users, the activities can be carried out in various interests such as entertainment, education, business and so on with the condition that if they have an access to an internet network connection. There is an network at the company PT. Satu Tujuan Kapital with the internet connection access, but the network architecture scheme is inadequate for that scope requirements as evidenced by signal strength testing with a value of -81 dBm and an output QOS parameter Throughput with a index value of 0 which is categorized as bad according to the TIPHON standard. The purpose of this research is to improve the quality of internet network quality based on QOS by implementing the development of Lan and wlan networks as a method to meet network needs within that scope. The test results are carried out via iperf by connecting a public server with the address iperf.biznetnetworks.com and wireshark as a data packet catcher, an increase is obtained with QOS results in the throughput parameter output which is worth 3 categorized as fair enough and there are also delay, jitter, and packet loss parameters that tends to be perfect and there is an increase in signal strength results with a value of -46 dBm from the client or user side.